Sistem Pengelolaan Limbah Plastik di Kota Lhokseumawe - Provinsi Aceh - Syaifuddin Yana; Dewi Mulyati; Badaruddin Badaruddin; Halimatussakdiah Halimatussakdiah (Jurnal Serambi Engineering, 2019)
The study aims to describe the plastic waste management from a processing perspective that has economic value added. Conversion of waste into an economic value, is one practice that can be a role of model, so that it can guide a certain region to do good and correct waste of management. The potential of Aceh’s plastic waste is relatively large, which must be considered by the regional government to be able to realize related to plastic waste processing  ctivities by the processor, where the existence is a large potential to be used as an opportunity for recycle. The current practice is still a little and only processing the plastic waste to become plastic chips, and there is no plastic waste processing  converted into processed plastic products. The existence of this processing can provide  conomic Added value for its owners  and provide benefits to  local governments as well. Therefore, it is need the role of  he Aceh government to bring up the spirit of entrepreneurship, especially in the management and processing of  lastic waste. On the other hand, a spirit of togetherness is needed through coordination and cooperation between local governments and non-governmental institutions, activists and environmentalists to carry out the mandate of the law relating to environmental conservation including waste management activities  that can be added to  conomic value.